Structure material physic-mechanical characteristics accuracy determination while changing the level of stresses in the structure - Kolokhov, Victor; Sopilniak, Artem; Gasii, Grygorii; Kolokhov, Alexander (International Journal of Engineering and Technology, 2018)
The reliability and durability of building structures is largely connected with the determination of the physic-mechanical characteristics (PMH) of a concrete structure, their measurement (determination) is the most critical procedure. The process of measuring physic-mechanical characteristics materials is characterized by various errors, which are divided into gross, systematic and random. The influence of systematic errors is taken into account by using various kinds of calibration (or gauging) dependencies which use non-destructive testing devices. The analysis of the presented results shows that the reliability of the belonging of concrete of different series to one general aggregate is rather low. This meant that the application of tariation dependencies, graduated for concrete in one series, will lead to significant errors in the determination of PMH for concrete of other series. Therefore, to clarify the physicomechanical characteristics of materials, it is necessary to use data on the level of stress-strain state of the structure.Â